2017
DOI: 10.21873/anticanres.12181
|View full text |Cite
|
Sign up to set email alerts
|

Anastomotic Leakage Using Linear Stapling Device with Pre-attached Bioabsorbable Polyglycolic Acid Felt After Laparoscopic Anterior Resection

Abstract: The frequency of anastomotic leakage was relatively low, and therefore the use of a linear stapler with pre-attached bioabsorbable PGA felt might reduce the risk of adverse events related to anastomosis, especially anastomotic leakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
(7 reference statements)
0
9
0
Order By: Relevance
“…However, that study contained a small proportion of patients with a high risk of bleeding (5% of patients took antithrombotics and 31% of patients showed resected specimen size $40 mm), hindering the comparability of the findings. We considered alternative studies using fibrin glue with a PGA sheet to calculate sample size (19,20,29,30), assuming that the preventive effect on post-ESD bleeding was mainly due to the fibrin glue's hemostatic effect rather than the PGA sheet because PGA sheets have been used as a reinforcing material to prevent anastomotic leakage in surgery (37,38) or perforation in ESD (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…However, that study contained a small proportion of patients with a high risk of bleeding (5% of patients took antithrombotics and 31% of patients showed resected specimen size $40 mm), hindering the comparability of the findings. We considered alternative studies using fibrin glue with a PGA sheet to calculate sample size (19,20,29,30), assuming that the preventive effect on post-ESD bleeding was mainly due to the fibrin glue's hemostatic effect rather than the PGA sheet because PGA sheets have been used as a reinforcing material to prevent anastomotic leakage in surgery (37,38) or perforation in ESD (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…A PGA sheet is a bio-absorbable suture reinforcement material recently reported to be effective for the endoscopic management of gastrointestinal leakage and perforation [ 8 ]. In rectal surgery, PGA has been used to reinforce staple lines and was reported to potentially be effective for reducing anastomotic leakage [ 9 , 10 ]. Therefore, we expected a PGA sheet with fibrin glue to be effective for treating RVF, even though there have been no previous reports of its application for anastomotic leakage after rectal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The reinforcement cartridge has previously been shown to be effective in preventing air leakage from lung resection margins in respiratory surgery [ 18 ] and dehiscence of staple lines in sleeve gastrectomy in bariatric surgery [ 19 ]. Yamamoto et al [ 20 ] reported a lower incidence rate of AL (1 of 62 cases [1.6%]) with the use of the reinforcement cartridge for rectal transection in rectal surgery. A prospective multicenter observational study to evaluate the efficacy and safety of the reinforcement cartridge for AL (trial ID: UMIN000029543) is also underway in Japan, and the results of this study are awaited.…”
Section: Double Stapling Techniquementioning
confidence: 99%